Differentiated Regional (Dis)Integration Post Brexit - M. V. Strezhneva (Vestnik MGIMO-Universiteta, 2022)
Exit of Britain from the European Union resuscitated academic discussions on the topic of the certainty value for the unfolding of disintegrative trends in the united Europe. Nevertheless, no general perception has emerged yet of how Brexit is likely to influence the organizational prospects and viability of the European integration grouping. In most cases the conceptualizations do not escape the presentation of dichotomy between integration and disintegration as two ultimo states in international relations. In fact, these are two processes, more complexly co-related. Each of them can include a wide array of structural arrangements, some differentiation dynamism, different levels of centralization in separate domains, as well as certain (variable) numbers of participants in distinct arrangements. In this article the meaning of Brexit as a condition of further European (dis)integration is treated, as based on Alexander Bogdanov’s theory of organization. This theory serves to reconsider the established renderings of such key notions, as integration, disintegration and differentiation.The new sight is gained of immune after-effects of prior Europeanization for the political system of the UK. Cases of the Economic and Monetary Union and the Northern Ireland Protocol receive separate treatment. The latter one presents a path-breaking design for differentiated integration with subnational region participation. Yet to realize the potential of the Protocol in full, political will is needed from both London and Brussels.On the most basic level, once this large country left the EU, one could hardly imagine any of its remaining 27 members to head off further progressive development of European integration. At the same time, it has to be acknowledged that, in order to make headway in terms of integration, the EU system, rather than unification and centralization, is in need of intensified differentiation. Meanwhile, the supranational institutions, and the European Commission most notably, remain oriented towards uniform integration as their priority. This can result in lower efficacy of the EU integration policy.